Řízení zásob během implementace nového informačního systému - Tyralíková, Alžběta (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Diplomová práce se zabývá řízením zásob při přechodu společnosti Sanmina-SCI Česká republika s. r. o. na nové informační systémy. Nejprve vysvětluje základní i odborné pojmy logistiky, informačních systémů a uvádí čtenáře do řešené problematiky. Další části práce se zabývají analýzou a návrhy možných řešení na zefektivnění plánování nákupu materiálových prvků.

This diploma thesis deals with inventory management during company transition Sanmina-SCI Česká republika s. r. o. to new information systems. First are explained the basic and specialized concepts of logistics, information systems and introduces related issues to the reader. Other parts of the thesis deal with analysis and suggestions for possible solutions to streamline planning of the purchase of material elements.
Supply Management During Implementation of New Information System
Keywords: Logistika; Nákupní proces; Zásoby; Sklad; Informační systémy; Logistics; Purchasing process; Inventory; Warehouse; Information systems